Graphene Fibers: Mussel‐Inspired Defect Engineering of Graphene Liquid Crystalline Fibers for Synergistic Enhancement of Mechanical Strength and Electrical Conductivity (Adv. Mater. 40/2018). Issue 40 (1st October 2018) - Kim, In Ho; Yun, Taeyeong; Kim, Jae‐Eun; Yu, Hayoung; Sasikala, Suchithra Padmajan; Lee, Kyung Eun; Koo, Sung Hwan; Hwang, Hoseong; Jung, Hong Ju; Park, Jeong Young; Jeong, Hyeon Su; Kim, Sang Ouk
Abstract : Inspired by mussel adhesive polydopamine (PDA), graphene‐based liquid‐crystalline fibers with high mechanical and electrical properties are prepared by Sang Ouk Kim and co‐workers, as described in article number1803267 . A two‐step defect engineering system is developed based on bioinspired surface polymerization and the subsequent solution infiltration of PDA enables the graphene fiber to overcome the intrinsic structural limitation during the fiber‐spinning process.